Postdependent state in rats as a model for medication development in alcoholism - Meinhardt, Marcus W.; Sommer, Wolfgang H. (Addiction biology, 2014)
Rational development of novel therapeutic strategies for alcoholism requires understanding of its underlying neurobiology and pathophysiology. Obtaining this knowledge largely relies on animal studies. Thus, choosing the appropriate animal model is one of the most critical steps in pre-clinical medication development. Among the range of animal models that have been used to investigate excessive alcohol consumption in rodents, the postdependent model stands out. It was specifically developed to test the role of negative affect as a key driving force in a perpetuating addiction cycle for alcoholism. Here, we will describe our approach to make rats dependent via chronic intermittent exposure to alcohol, discuss the validity of this model, and compare it with other commonly used animal models of alcoholism. We will summarize evidence that postdependent rats fulfill several criteria of a ‘Diagnostic and Statistical Manual of Mental Disorders IV/V-like’ diagnostic system. Importantly, these animals show long-lasting excessive consumption of and increased motivation for alcohol, and evidence for loss of control over alcohol intake. Our conclusion that postdependent rats are an excellent model for medication development for alcoholism is underscored by a summary of more than two dozen pharmacological tests aimed at reversing these abnormal alcohol responses. We will end with open questions on the use of this model. In the tradition of the Sanchis-Segura and Spanagel review, we provide comic strips that illustrate the postdependent procedure and relevant phenotypes in this review.
Gesehen am 30.08.2017